Mathematical Models of Water and Solute Transport in Soil - Agah, A. Erfani; Meire, P.; Deckere, E. De (Journal of Applied Solution Chemistry and Modeling, 2017)
Improved understanding of water flow and solute transport through the unsaturated zone is important for the sustainable management of soils. As soils are complex and heterogeneous systems, quantification of the transport processes is difficult. More knowledge on the relationship between solute transport process, soil structure, hydrologic initial and boundary conditions, and observation scale is needed here.Modeling unsaturated flow and transport with mathematical or numerical methods is an important tool for predicting the infiltration and redistribution of soil water and the transport of solutes in the unsaturated zone. Flow and transport models are commonly used to support the decision making process in agricultural management, environmental impact assessment, toxic waste control, remediation design, and subsurface cleanup monitoring. The movement of contaminants through porou media describs by the combination of advection, diffusion-dispersion and chemical retardation. The most common model that describes solute transport by convection and dispersion is the convection-dispersion equation (CDE). This equation describes the change in concentration at any point along the flow path as a function of time. This paper is mainly dedicated to a discussion of basic processes for modelling of water flow and contaminant transport in saturated and unsaturated soils. After a brief description of the classical approach for simulating water flow and solute transport in porous media, issues related to water and solute trasport equation in soil.